2016
DOI: 10.1051/0004-6361/201628798
|View full text |Cite
|
Sign up to set email alerts
|

Accretion disks in Algols: Progenitors and evolution

Abstract: Context. There are only a few Algols with measured accretion disk parameters. These measurements provide additional constraints for tracing the origin of individual systems, narrowing down the initial parameter space. Aims. We investigate the origin and evolution of six Algol systems with accretion disks to find the initial parameters and evolutionary constraints for them. Methods. With a modified binary evolution code, series of close binary evolution are calculated to obtain the best match for observed indiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
(73 reference statements)
0
7
0
1
Order By: Relevance
“…In order to avoid the random number f sync , Van Rensbergen & De Greve [14] calculated t sync with a physical model, distinguishing convective from radiative envelopes. Hurley et al [21] use an expression of Hut [22] to calculate t sync for a star with a convective envelope.…”
Section: Tidal Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid the random number f sync , Van Rensbergen & De Greve [14] calculated t sync with a physical model, distinguishing convective from radiative envelopes. Hurley et al [21] use an expression of Hut [22] to calculate t sync for a star with a convective envelope.…”
Section: Tidal Interactionmentioning
confidence: 99%
“…In the papers [12,13], we investigated mass loss from the system (the liberal case) during eras of rapid mass transfer, while using a hot spot mechanism. In [14], we presented models for systems with an accretion disk. Equatorial velocities of gainers were modelled in [15] using magnetic braking to keep the equatorial velocity far below critical during the evolution of the binary.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that a binary with an ongoing mass transfer is a reasonable explanation for both components of the HD 81357 system. A more detailed modelling including an accretion disk, as carried out by Van Rensbergen & De Greve (2016) for other Algols, would be desirable.…”
Section: Stellar Evolution Of Hd 81357 With Mass Exchangementioning
confidence: 99%
“…Our previous work (Van Rensbergen & De Greve 2008) used tidal interaction according to Wellstein (2001). In a subsequent paper, Van Rensbergen & De Greve (2016) included a more refined treatment of tidal interactions. Hereinafter, tides for a star with a radiative atmosphere are very different to those of a star in convection (see e.g.…”
Section: Introductionmentioning
confidence: 99%